Software Development For Conversion Of Ip To Wireless Atm (Watm) - Sudhakar, Swarnappa Clement (2002)
To meet the anticipated and high demand for wireless access to the broadband Asynchronous Transfer mode (ATM) network, the concept of wireless ATM has been proposed in 1994. One of the main challenge in the design of the Wireless ATM network resides in the formation of the Wireless MAC protocol, that could handle various services with a considerable QoS and providing efficient utilization of the Wireless Channel. In this thesis, we propose the conversion algorithm that leads to a WATM packet assuming to use the TCP/IP protocol as the source. The project considers the various aspects of carrying IP over a WATM channel, by retransforming the IP data to a WATM cell, ready to be transmitted over a wireless channel.Analysis and simulation shows various advantages and disadvantages in the above-mentioned method when performed using software. Furthermore, discussion about the hardware methods of implementing communication protocols shows a way for the engineer to choose the right method for his future development of the protocols for implementation. Finally, this algorithmic approach is proposed to integrate this approach to simulate the methodology of IP to WATM conversion.